Relação entre oralidade e escrita nas práticas discursivas do afásico. - Gomes, Izabella Cristina de Aguiar (2010)
Aphasia is considered a reduction and dysfunction of the use of the language in which there is alteration of linguistic mechanisms in all the levels, shown in the expressive aspect how much in the receptive one of the oral and written language to different degrees in each type. The presupposition used in this work is that the language, while symbolic process, leaves from a social context, and acts like social practice, showing and working like oral and written activity in the constitutive activities of the man with which we can build senses. Between these two kinds of the language, the orality occupies a place of distinction regarding the writing in the studies on Aphasia. Before this, this work would be done to tackle the written production of the aphasic person in his relation with the orality, aiming to check in the written production of the aphasic at “possible” present marks of orality or not in the oral expression of this subject. For this objective, the written productions of 6 (six) subjects were selected. Aphasic people of both types, which announced and frequented regularly the Group of Familiarity for Aphasic people of the Catholic University of Pernambuco, during the period of 22 (twenty two) meetings. The studies for the presented subject were based on damages to the organization of the speech of the aphasic people and on the theoretical detailed studies on speech and writing, detaching the relation between these two kinds of the language. With that, one could check the presence of 10 (ten) types of marks of oralities in the written productions of the aphasic person involved in this work through activities with 6 (six) textual types developed through the realization of the Workshop of Speech and Written in the Group. When the correction is standing out by the most frequent mark of orality, this is present in the writing of 5 (five) subjects. The relevance of the work identifies characteristics and it offers strategies for overcoming of the difficulties faced by this citizen, looking to contribute to the development and improvement of the restoration of his language, using all the resources used by the aphasic person to communicate, when there is making possible an intervention which approach so much the speech as for writing, contributing to the readaptation of the orality and to a recuperation more effective of the language as a whole, promoting the social re-insertion of the aphasic citizen in his environment. Keywords: aphasia, relation between orality – written, textual types, mark of orality.